Enhanced Relative Humidity Sensor via Diameter of No-Core Fiber Structure - Al-Swefee, Huda T.; Al-Hayali(, Sarah K.; Al-Janabi, Abdulhadi A. (Iraqi Journal of Laser, 2019)
Single mode-no core-single mode fiber structure with a section of tuned no-core fiber diameter to sense changes in relative humidity has been experimentally demonstrated. The sensor performance with tuned NCF diameter was investigated to maximize the evanescent fields. Different tuned diameters of of (100, 80, and 60)μm were obtained by chemical etching process based on hydrofluoric acid immersion. The highest wavelength sensitivity was obtained 184.57 pm/RH% in the RH range of 30% –100% when the no-core fiber diameter diameter was 60 μm and the sensor response was in real-time measurements